Librarians: My perspectives / Siti Nur Aishah Mansor - Mansor, Siti Nur Aishah (Faculty of Information Management, 2014)
The purpose of this article is to express my opinion on the perspective I had towards librarians before I studied in Faculty of Information Management and learn on librarianship. Before I studied about librarianship during my diploma, I never realize the uniqueness of the profession as a librarian. I used to underestimate the responsibilities of a librarian in the development and the effectiveness of a library. During my studies in UniversitiTeknologi MARA Segamat in Diploma of Information Management, I was exposed to the reality of a librarian and what the library actually is about. Therefore, here I tried to state my experiences and opinions on the perspective of a user of a library and my encounter with librarians.